Brain oscillations and athletic performance - Mierau, A.; Hülsdünker, T.; Strüder, H. K. (Sports Performance, 2015)
Large populations of synchronously active cortical neurons produce oscillations which can be measured on the surface of the scalp using electroencephalography (EEG). These cortical oscillations can be analysed in the frequency domain. Power in different frequency bands (e.g. delta, theta, alpha, beta and gamma) has been shown to correlate with specific perceptual, sensorimotor or cognitive processes. Therefore, cortical oscillations can be used to better understand how the cortex is involved during accomplishment of different tasks. This chapter discusses research addressing the relationship between cortical oscillations and sport performance in ecologically valid settings (Sect. 3.1). Since balance ability has been suggested to play a crucial role for performance in various sports, this chapter also reviews studies describing brain activity during balance control (Sect. 3.2). For a more complete analysis, experiments where EEG neurofeedback training was applied to enhance sport performance will also be taken into consideration (Sect. 3.3). Finally, some concluding remarks and suggestions for future research will be outlined (Sect. 3.4).